Matka Królów - Zaorski, Janusz (Poland, 1983)
Made in 1982, shelved for five years. The story opens with Lucja Krol's husband falling under a tram. She gives birth to her fourth son on the floor of their new apartment. Neighbor Wiktor, a communist intellectual, befriends the poverty-stricken family but is soon arrested and sent to jail. During the war Lucja narrowly escapes a Nazi roundup at the black market. Her sons hold ardent Communist meetings in their apartment, with her blessing. Lucja works hard, but without complaining. After the war, Klemens is inexplicably arrested, accused by the new regime of being a collaborator. Wiktor, now a high-ranking party member, trying to defend him, but himself falls into disgrace. Klemens is tortured to "confess" and dies in jail, a Communist to the end. Lucja is never told about his fate.
Keywords: Fiction films